The deuterium excess records of EPICA Dome C and Dronning Maud Land ice cores (East Antarctica) - STENNI, BARBARA; Masson Delmotte V.; Selmo E.; Oerter H.; Meyer H.; Röthlisberger R.; Jouzel J.; Cattani O.; Falourd S.; Fischer H.; Hoffmann G.; Iacumin P.; et al. (Quaternary Science Reviews, 2010)
New high-resolution deuterium excess (d) data from the two EPICA ice cores drilled in Dronning Maud Land (EDML) and Dome C (EDC) are presented here. The main moisture sources for precipitation at EDC and EDML are located in the Indian Ocean and Atlantic Ocean, respectively. The more southward moisture origin for EDML is reflected in a lower present-day d value, compared to EDC. The EDML andEDC isotopic records (d18O and d) show the main climate features common to the East Antarctic plateau and similar millennial scale climate variability during the last glacial period. However, quite large d18O and d differences are observed during MIS5.5 and the glacial inception with a long-term behaviour. A possibility for this long-term difference could be related to uncertainties in past accumulation rate which are used in the glaciological models. Regional climate anomalies between the two sites during MIS5.5 could also be consistent with the observed EDML-EDC d18O and d gradient anomalies. Simulations performed with the General Circulation Model ECHAM4 for different time slices provide a temporal temperature/isotope slope for the EDML region in fair agreement to the modern spatial slope. Tsite and Tsource records are extracted from both ice cores, using a modelling approach, after corrections for past d18O seawater and elevation changes. A limited impact of d on Antarctic temperature reconstruction at both EDML and EDC has been found with a higher impact only at glacial inception. The AIM (Antarctic Isotope Maximum) events in both ice cores are visible also after the source correction, suggesting that these are real climate features of the glacial period. The different shape of the AIM events between EDC and EDML, as well as some climate features in the early Holocene, points to a slightly different climate evolution at regional scale. A comparison of our temperature reconstruction profiles with the aerosol fluxes show a strong coupling of the nssCa fluxes with Antarctic temperatures during glacial period and a tighter ...